Effects of organic and inorganic fertilizers on growth and yield of Vigna unguiculata subsp. Sesquipedalis L. (Verdc.) - Siti Naimah S. (2021)
A field study was conducted to examine the effects of organic and inorganic fertilizers on growth and yield of yard long bean, Vigna unguiculata Subsp. sesquipedalis L.. Three rates (14.5 g, 11.2 g, 17.8 g/plant) of organic fertilizer (poultry manure) and three rates (5 g, 3 g, 7 g/plant) of inorganic fertilizer which is NPK blue special (12:12:17:2) were evaluated to study the growth and yield of yard long bean. The experimental design used was Completely Randomized Design (CRD) with three replications. The application of fertilizer had significant effect on number of leaves and plant height but no significant effect on the chlorophyll content. The yield was also increased from two pods at a rate of 7 g of NPK blue special/plant to 16 pods at a rate of 14.5 g of poultry manure/plant. This study showed that the rate of fertilizer application for different types of fertilizers was not significant on the growth and yield parameters of yard long bean. The use of poultry manure at the rate of 17.8 g/plant was probably more suitable to elevate the growth and yield of yard long bean instead of using inorganic fertilizer.